2023
DOI: 10.1057/s41264-022-00202-8
|View full text |Cite
|
Sign up to set email alerts
|

What drives the investment intentions of emerging economy millennials? Examining the effect of financial advertisement with the PLS-SEM

Abstract: The financial service sector involves high-risk and uncertain elements that make financial decision-making challenging; thus, information sources act as facilitators. The present study analyzed the effects of financial advertisements on investors’ behavioral intentions with perceived risk acting as a mediator and gender and marital status as moderating variables. The study empirically validates the proposed conceptual model (based on Stimulus–Organism–Response) with the interrelationship between financial adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 142 publications
2
5
0
Order By: Relevance
“…Thus, H1 is accepted, signifying that a higher risk appetite leads to increased willingness to participate in the risky financial market. Results in line with this study were previously reported by Ishfaq et al (2020) and Dogra et al (2023). Shehata et al (2021) reported that higher awareness on risk enhances an investor's confidence while trading in the stock market.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, H1 is accepted, signifying that a higher risk appetite leads to increased willingness to participate in the risky financial market. Results in line with this study were previously reported by Ishfaq et al (2020) and Dogra et al (2023). Shehata et al (2021) reported that higher awareness on risk enhances an investor's confidence while trading in the stock market.…”
Section: Resultssupporting
confidence: 92%
“…Results in line with this study were previously reported by Ishfaq et al . (2020) and Dogra et al . (2023).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Individuals with greater financial literacy tend to make better investment decisions, leading to increased financial satisfaction (Sobaih & Elshaer, 2023). Also, financial behavior of individuals also exerts an influence on their investment choices, which in turn have an impact on their level of financial satisfaction (Dogra, Kaushal & Kalia, 2023). Investment choices have been shown to have a mediating role in the relationship between financial literacy, financial behavior, and financial satisfaction, as demonstrated by the research in relevant academic fields.…”
Section: Introductionmentioning
confidence: 95%